The presence of teaching barriers in children with autism - Arsić, Bojana; Lukic, Ana; Gajic, Anja (Norma, 2022)
The aim of this research was to examine the most common barriers faced by special education teachers in working with children with autism spectrum disorders (ASD). The sample included 53 participants of both genders and of different ages who were diagnosed with ASD. The instrument used to assess the presence of barriers in teaching refers to the Assessment of Barriers in Teaching (VB-Mapp Barriers Assessment - Sundberg, 2008). In our sample, it was found that all respondents have a pronounced presence of teaching barriers, while the most frequent barriers are prompt dependence, generalization difficulties, socialization problems, mand deficits, escape or avoidance of given tasks and the absence of the tact ability. Having in mind the obtained results, it is highlighted as a necessity to develop an approach that would lead to the elimination of the mentioned barriers, as well as to develop a treatment plan to address those teaching barriers in working with children with PSA and consequently enable a higher degree of adoption of new knowledge and skills by children with ASD.